From Knowledge Assets to Brand Equity: The Role of Integrated Marketing Communication and Social Media in Indonesian Private Universities - Junaid Ali Saeed Rana (Journal of Marketing Innovation (JMI), 2026)
This study examines how private universities in Indonesia translate strategic capabilities into customer-based brand equity (CBBE) through communication strategies. Using the resource-based view, it defines sustainable competitive advantage (SCA) as a marketing-enabling capability and explores the roles of integrated marketing communication (IMC) and social media adoption (SMA) within a unified framework. A quantitative method was used to collect survey data from 411 students at the five largest private universities in DKI Jakarta, and the data were analyzed using structural equation modeling. The results reveal that SCA significantly boosts both IMC and SMA, but only IMC, directly and indirectly, enhances CBBE, emphasizing the importance of communication consistency in translating institutional strengths into brand value. This study introduces the following innovations: (1) redefining SCA as a marketing-enabling capability rather than just a strategic result, (2) integrating SCA, IMC, SMA, and CBBE into a single explanatory model within the higher education setting, and (3) empirically showing that IMC fully mediates the relationship between SCA and CBBE, while SMA does not. Practically, the findings suggest universities should use cohesive communication strategies and align digital efforts to strengthen brand equity in competitive higher education markets.